Experiences of living with developmental dysplasia of the hip in adults not eligible for surgical treatment: a qualitative study - Julie Sandell Jacobsen; Martin Dan Jorgensen; Sarah Bournonville Frederiksen; Dorthe Sørensen (BMJ Open)
Objectives Adults with developmental dysplasia of the hip face barriers in their everyday lives due to pain and physical limitations. In Denmark, some patients may not be eligible for hip-preserving surgery due to being overweight, hip osteoarthritis, age above 45 years, negative impingement test or not wishing to undergo surgery. These patients are left with no evidence-based treatment option. The patient perspective when not being eligible for surgery has not yet been investigated. This study aimed to explore the experiences of living with developmental dysplasia of the hip in adults not eligible for hip-preserving surgery.Design and participants In this qualitative study, we used a phenomenological–hermeneutic approach to explore the experiences of living with developmental dysplasia of the hip. We conducted semistructured interviews with 17 purposefully selected patients (median age 37 (range 19–50) years). The patients were recruited from a population of 30 patients included in a larger feasibility study evaluating a 6-month exercise and patient education intervention. We used a ricoeur-inspired method to analyse and interpret the interview data.Results Three themes were identified. First, developmental dysplasia of the hip is more than just a joint disease. Second, living with pain is difficult when pain has its own life. Third, limitations imposed by hip problems challenge the perception of oneself as young, active and independent. Identity, meaningfulness, control over pain and coping with pain were areas of the patients’ lives that were influenced.Conclusion Living with developmental dysplasia of the hip had a considerable impact on the patients of this study and their everyday life in several areas. Therefore, it may be relevant to approach patients with developmental dysplasia of the hip from a biopsychosocial point of view. However, further research is required to obtain a better understanding of the experiences of living with developmental dysplasia of the hip.